ANALISIS STRUKTUR BATIN PUISI “SENJA DI PELABUHAN KECIL” KARYA CHAIRIL ANWAR - Muhamad Abdul Rohman (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
This This research is motivated by researchers' curiosity about the poetry of a Chairil Anwar someone who makes poetry as a vehicle to express the expression of expressionism and realism of a soul of Chairil Anwar. Soul expressions and poetry are two things that are difficult to find correlation. Through this poem "Dusk in the Small Port", Chairil Anwar crystallizes an expression of his soul which is deposited in lines and stanzas, thus creating an ambiguity of meaning in each poetry structure. The formulation of the problem that the researcher analyzes in this study is how is an inner structure embedded in the poem? The purpose of this study is to describe the inner structure, namely the theme, tone and feeling, atmosphere, and message. With reference to analyzing the structure of the inner content of poetry by reviewing it concretely and clearly. The method prepared by the researcher is descriptive qualitative. The results obtained with respect to the analysis of researchers can be concluded that this poem is a type of lyrics that is packaged with different perspectives, evidenced by the theme of individual overflows, soft tones with various sudden contents of experience as well as the various attitudes of the author and the inner situations that surround them, tastes and situations that surround them far right in the work is full of dramatic, and the mandate of the author as well as the writer who delivered substantial imperative to the reader.